Two-stage repeated-batch fermentation of immobilized Clostridium beijerinckii on oil palm fronds for solvents production. Issue 8 (August 2015) - Loyarkat, Sawang; Cheirsilp, Benjamas; Prasertsan, Poonsuk
Graphical abstract: Highlights: Oil palm fronds (OPF) are potential support materials for clostridium immobilization. Immobilized cells on OPF produced high butanol in repeated-batch fermentation. Two-stage repeated-batch fermentation improved solvent productivity. Abstract: In this study, palm tree wastes including oil palm shells, palm press fibers, empty fruit bunches and oil palm fronds were evaluated as possible eco-friendly support materials for immobilization of solvent-producing Clostridium beijerinckii . Among support materials tested, oil palm fronds are the most suitable support materials for cell immobilization and repeated-batch production of solvents by non-growing cells incubated in nitrogen-free medium. The non-growing immobilized cells on 7% (w/v) oil palm fronds produced the highest solvent yield of 12.2 g/L in the 1st batch. However, in the 2nd and 3rd batches the solvent production was reduced to 9.01 g/L and 4.95 g/L, respectively. Two-stage repeated-batch fermentation in which immobilized cells were re-incubated in nitrogen-rich medium (Stage I) before being re-used in nitrogen-free medium (Stage II), were then attempted. The solvents produced by this strategy remained >80% in the 3rd cycle and >55% in the 4th cycle. The total solvent yields in the 1st, 2nd, 3rd and 4th cycles were as high as 31.5, 30.6, 25.3 and 17.5 g/L, respectively. This study has shown that lignocellulosic palm tree wastes can be used as low-cost support materials for immobilization of clostridia and the solvent productivity can be improved by two-stage repeated-batch fermentation.